2004
DOI: 10.1128/iai.72.1.602-605.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Anthrax Toxemia by Hexa- d -Arginine In Vitro and In Vivo

Abstract: The anthrax toxin protective antigen precursor is activated by proteolytic cleavage by furin or a furin-like protease. We present here data demonstrating that the small stable furin inhibitor hexa-D-arginine amide delays anthrax toxin-induced toxemia both in cells and in live animals, suggesting that furin inhibition may represent a reasonable avenue for therapeutic intervention in anthrax.Anthrax toxin consists of three polypeptides, the protective antigen (PA), lethal factor (LF), and edema factor (EF) (revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Furin inhibitors that prevent the activation of bacterial toxins, such as anthrax toxin (40), are under development. Results from mice protected against anthrax toxemia by systemic treatment with furin inhibitors suggest that topical application might have acceptable side effects (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furin inhibitors that prevent the activation of bacterial toxins, such as anthrax toxin (40), are under development. Results from mice protected against anthrax toxemia by systemic treatment with furin inhibitors suggest that topical application might have acceptable side effects (41).…”
Section: Discussionmentioning
confidence: 99%
“…Protection of Anthrax Toxemia by D9R Amide in RAW264.7 Cells-Previous studies showed that the D6R amide prevents anthrax toxemia in RAW cells by inhibiting PA cleavage (9). Because D9R amide exhibited a better K i for furin in enzymatic assays, we tested whether this nonamer is also more potent in blocking anthrax toxemia (Fig.…”
Section: D9r Is a Highly Potent Furin Inhibitormentioning
confidence: 98%
“…L6R (hexa-L-arginine), 1 for example, exhibits the low inhibition constant (K i ) of 114 nM (7), and the D-forms of these polyarginines were also shown to be inhibitory. Moreover, D6R amide has been shown to block the activation of Pseudomonas aeruginosa exotoxin A (8) and to protect against anthrax toxemia both in vivo and in vitro (9).…”
mentioning
confidence: 99%
“…Mutant forms of the PA molecule (dominant-negative inhibitors) with abnormal 2␤2-2 ␤3 loops that form dysfunctional heptamers with wild-type PA prevented the uptake and transport of LF or EF and were effective with LeTx challenge in cell culture and Fisher 344 rats (80,81). Hexa-d-arginine, a furin inhibitor that blocks PA cleavage and heptamer formation, was protective with LeTx challenge in murine alveolar macrophages and Fisher 344 rats (82). Finally, soluble PA receptor protected against LeTx in in vitro studies (13).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%